Efficient Strategies for a Medium Voltage Loop Powered by an Infinite Source - Mahmoud, Ethmane Isselem Arbih; Abbou, Ahmed; Mahmoud, Abdel Kader; Eida, Né Dah (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2025)
This paper analyzes and examines the potential of an infinite generation system to support the domestic load growth of the 33 kV loop network from 2025 to the year 2040. The study assesses the current state of the network, focusing on voltage levels, line loadings, and transformer capacities to ensure that all components operate within the system's allowable loading limits. It is assumed that the loop is powered by an infinite source. A numerical model, utilizing the Gauss-Seidel method, is developed and run using the PSS/E simulator and ETAP. The voltage profile is expected to remain within the range of 0.95 to 1.05 pu. An analysis of the simulation results demonstrates the potential for increasing active power transfer and controlling reactive power in the system by the year 2040.Furthermore, solutions are proposed to address identified critical issues in order to meet the projected demand. These include doubling the capacity of existing transformers and implementing protection against short-circuit currents. The proposed system is expected to provide industrial consumers with reduced load imbalances and improved control over voltage fluctuations caused by rapid changes in reactive power demand.